Non-volatile memory device using a polymer modified nanocrystal - Kiazadeh, Asal (2013)
Thin-film planar structures using AgCl nanocrystals embedded in a polymer blend; exhibit reliable and reproducible switching between different non-volatile conductance states. It is shown that resistive switching in these systems cannot be related with migration diffusion or aggregation of metals to form metallic filaments. This is supported by temperature-dependent measurement showing that the current in the high conductance state is thermal activated (0.6 eV).